Faktor Yang Mempengaruhi Tingkat Suku Bunga Deposito Bank Umum Di Indonesia - Oktavia Dwi Haryanti; Rian Destiningsih (Jurnal Ekonomi Pembangunan, 2021)
BBanks are financial institutions involved in the state development process that provide services to the public and have functions, such as raising funds. Banks cannot carry out their tasks properly if there are no funds; one of the ways the banks attract the public to raise funds is the time deposit interest rate. This study aims to determine what factors can affect commercial banks' deposit rates in Indonesia from 2010 to 2019. This research method uses multiple regression analysis techniques using the Vector Error Correction Model (VECM) method using secondary data. The results of this study indicate that the BI rate significantly affects the deposit rate. Inflation significantly affects deposit rates. Meanwhile, economic growth does not affect substantially deposit rates. The estimation results of the VECM model show that there is a significant effect in the long run but not substantial in the short term.